1996
DOI: 10.1095/biolreprod54.6.1420
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epidermal Growth Factor in Bovine Oocyte Maturation and Preimplantation Embryo Development in Vitro1

Abstract: Epidermal growth factor (EGF) has been shown to have a positive effect during in vitro maturation (IVM) and has been reported in follicular fluid at levels capable of stimulating meiosis in a variety of species. The aim of the present work was to study the effect on subsequent development of EGF present in defined medium during bovine 1) oocyte maturation or 2) embryo culture. The presence of EGF during IVM, irrespective of concentration (1, 10, 100 ng/mg), stimulated cumulus expansion and significantly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
169
3
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(180 citation statements)
references
References 62 publications
5
169
3
3
Order By: Relevance
“…In this sense, some authors observed no beneficial effects of EGF in the embryo CM on the blastocyst rate either in individual (mouse: O'Neill, 1997, 0.2 to 2000 ng/ ml; bovine: Keefer et al, 1994, 10 ng/ml) or in group culture (bovine: Flood et al, 1993, 10 ng/ml, Shamsuddin, 1994, 10 to 50 ng/ml, Lee and Fukui, 1995, 10 ng/ml). However, other authors observed differences both in single (mouse: Paria and Dey, 1990, 10 ng/ml; bovine: Lim et al, 2007, 10 ng/ml) and group culture (bovine: Lonergan et al, 1996, 100 ng/ml; Mtango et al, 2003, 10 ng/ml;, 5 ng/ml). On the other hand, the effect of TGF-a was also evaluated in the present work, and no beneficial effects, but rather negative, of this GF on embryo development were found, confirming results previously showed by other authors observing no beneficial effects (Brison and Schultz, 1997;Zhou et al, 2008).…”
Section: Discussionmentioning
confidence: 87%
“…In this sense, some authors observed no beneficial effects of EGF in the embryo CM on the blastocyst rate either in individual (mouse: O'Neill, 1997, 0.2 to 2000 ng/ ml; bovine: Keefer et al, 1994, 10 ng/ml) or in group culture (bovine: Flood et al, 1993, 10 ng/ml, Shamsuddin, 1994, 10 to 50 ng/ml, Lee and Fukui, 1995, 10 ng/ml). However, other authors observed differences both in single (mouse: Paria and Dey, 1990, 10 ng/ml; bovine: Lim et al, 2007, 10 ng/ml) and group culture (bovine: Lonergan et al, 1996, 100 ng/ml; Mtango et al, 2003, 10 ng/ml;, 5 ng/ml). On the other hand, the effect of TGF-a was also evaluated in the present work, and no beneficial effects, but rather negative, of this GF on embryo development were found, confirming results previously showed by other authors observing no beneficial effects (Brison and Schultz, 1997;Zhou et al, 2008).…”
Section: Discussionmentioning
confidence: 87%
“…Likewise, it is possible that the growth factors may play critical roles in oocyte maturation by stimulating the pattern of proteins neosynthesized during oocyte maturation [40], and play a regulatory role in oocyte maturation in a paracrine/autocrine manner, or it might be one of the signaling factors for the resumption of meiosis in oocytes [62]. The growth factors have been shown to accelerate progression of meiosis [63] and the meiotic cell cycle in bovine oocytes, possibly by increasing H1 and MAP kinase activity during the early stages of maturation [64].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that epidermal growth factor (EGF) stimulates the IVM of oocytes in mice [39], cattle [40], humans [41] and pigs [42]. Activin, transforming growth factor beta (TGF-b), and basic fibroblast growth factors (bFGF) have been shown to stimulate the mitotic activity of bovine granulosa cells and/or the growth of granulosa cells or follicles in culture [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Paraffin oil [10][11][12], mineral oil [13][14][15] and silicone oil [16,17] have been broadly used to protect culture medium from evaporation and contamination when early embryos are cultured. Further studies have indicated that the application of oil affects the embryo development either in a positive or a negative way [18,19].…”
Section: Introductionmentioning
confidence: 99%